On the role of mechanics in driving mesenchymal-to-epithelial transitions - Kim, Hye Young; Jackson, Timothy R.; Davidson, Lance A. (Seminars in cell & developmental biology, 2017)
[Display omitted] •Mechanical cues initiate, propagate, and stabilize polarization in MET.•Spectrum of METs range from all-at-once epithelialization to single cell METs.•Early development, organogenesis, cancer progression share basic MET framework.•Comparative analysis of MET and their relation to EMTs needs to be explored further. The mesenchymal-to-epithelial transition (MET) is an intrinsically mechanical process describing a multi-step progression where autonomous mesenchymal cells gradually become tightly linked, polarized epithelial cells. METs are fundamental to a wide range of biological processes, including the evolution of multicellular organisms, generation of primary and secondary epithelia during development and organogenesis, and the progression of diseases including cancer. In these cases, there is an interplay between the establishment of cell polarity and the mechanics of neighboring cells and microenvironment. In this review, we highlight a spectrum of METs found in normal development as well as in pathological lesions, and provide insight into the critical role mechanics play at each step. We define MET as an independent process, distinct from a reverse-EMT, and propose questions to further explore the cellular and physical mechanisms of MET.